2011
DOI: 10.1016/j.cell.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

MAVS Forms Functional Prion-like Aggregates to Activate and Propagate Antiviral Innate Immune Response

Abstract: In the graphical abstract for the article above, the word ''interferons'' was inadvertently misspelled as ''interterons.'' The graphical abstract has been corrected and is now available online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
172
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(182 citation statements)
references
References 0 publications
10
172
0
Order By: Relevance
“…2) [27•]. Interactions between these two CARD domains result in the formation of a prion-like signaling platform essential for MDA5-mediated signaling [32]. The organization of the MAVS filament structure along the mitochondrial membrane recruits signaling intermediates including TNF receptor-associated factors 2 and 6 (TRAF 2, 6).…”
Section: Mda5/ifih1 Viral Sensing and Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…2) [27•]. Interactions between these two CARD domains result in the formation of a prion-like signaling platform essential for MDA5-mediated signaling [32]. The organization of the MAVS filament structure along the mitochondrial membrane recruits signaling intermediates including TNF receptor-associated factors 2 and 6 (TRAF 2, 6).…”
Section: Mda5/ifih1 Viral Sensing and Signalingmentioning
confidence: 99%
“…The organization of the MAVS filament structure along the mitochondrial membrane recruits signaling intermediates including TNF receptor-associated factors 2 and 6 (TRAF 2, 6). While IKKβ, TBK1, and IRF3 were not found to be recruited to the MAVS filament structure, a specific MAVS domain containing three binding motifs for TRAF was required for IRF3 dimerization and IFNβ expression [32]. Additionally, deletional analysis of the TRAF-binding domain has shown that the entire domain is essential for IL-6 expression while only one of three TRAF-binding motifs are required for IFNβ expression [33].…”
Section: Mda5/ifih1 Viral Sensing and Signalingmentioning
confidence: 99%
“…Subsequently, the CARDs of RLRs mediate their binding to the mitochondrial outer membrane protein MAVS (also known as IPS1, VISA or Cardif) and induce the prion-like aggregation and activation of MAVS [31]. In turn, MAVS polymers recruit several adaptor proteins including TNF receptor associated factors (TRAFs), TNFR-associated death domain-containing protein (TRADD) and TOM70, ultimately leading to the activation of TBK1 and IRF3 [32][33][34][35][36].…”
Section: Essential Roles Of Poly-ubiquitination In Rlr Signaling Pathmentioning
confidence: 99%
“…This activated complex of RIG-I is then able to interact with its adapter MAVS [90], also known as IPS-1, Cardif and VISA [91][92][93], promoting aggregation of MAVS [94], and redistribution of MAVS and mitochondria [95]. This unique tetrameric structure of RIG-I possibly promotes the formation of a seed fiber of MAVS, which then results in the three-stranded prion-like fibers in cells that robustly activate downstream signaling [96][97][98]. The exact mechanism for the formation of a seed fiber of MAVS and how different RIG-I-RNA complexes activate MAVS remains unknown.…”
Section: Mechanism Of Activation Of Rig-imentioning
confidence: 99%